Transformações na estrutura produtiva da economia paranaense nos anos 80 e 90 (Economia Aplicada, 2007)
This article presents the evolution of the productive structure of the economy of the State of Paraná in the 1980's and 1990's. A set of 5 regional input-output matrices, divided in 32 sectors, was estimated for the years of 1980, 1985, 1990, 1995 and 1999, in order to calculate the field of influence, the Hirschman-Rasmussen and pure linkages and the sectors multipliers. These indicators allowed to identify, besides the key sectors, the evolution of economic and inter-industrial relationships in the period. The results showed trends of diversification in the productive structure of State and of greater commercial opening, both reflected in fewer internal linkages and in production multipliers.